NEGOTIATING AI IN CRAFT-BASED PRINTMAKING: A PHENOMENOLOGICAL STUDY OF THE MINGGIRAN COMMUNITY, INDONESIA - Fatihah, Amabel Janitra; Wahyu Utama , Aji Prasetya (Fakultas Ilmu Budaya, Universitas Brawijaya, 2026)
Abstract The Fourth Industrial Revolution is reshaping fine-art practice, including traditional printmaking. This qualitative phenomenological study examines how artists in the Minggiran Graphics Community (Yogyakarta) perceive the integration of artificial intelligence (AI) into conventional print processes. Data were collected through semi-structured interviews with seven purposively selected informants, participant observation, and document analysis over seven months (September 2024–April 2025). Thematic analysis yielded three key findings: (1) community perceptions of AI are ambivalent—some members embrace it as an exploratory aid while the majority preserve manual processes; (2) AI adoption remains individual and has not integrated into collective practice; (3) core printmaking values, process authenticity, material exploration, and handcraft—constitute the primary barrier to adoption. Applying Rogers’ Diffusion of Innovation Theory, this study finds that slow AI adoption stems not from lack of awareness but from incompatibility with collective community values. Keywords: Artificial Intelligence; Traditional Printmaking; Minggiran Graphics Community; Phenomenology; Diffusion of Innovation